2017
DOI: 10.1016/s1470-2045(17)30373-x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic approaches to accelerate cancer interception

Abstract: Summary While the last decade has witnessed major advances in the treatment of late stage cancers with targeted and immune-based therapies, there is a critical unmet need to develop new approaches to impact the prevention and early detection of cancer. Recent advances in the field of genomics and computational biology offer unprecedented opportunities to understand the earliest molecular events associated with carcinogenesis, leading to novel strategies to intercept the development of invasive cancers. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 98 publications
(73 reference statements)
1
33
0
Order By: Relevance
“…Moreover, it demonstrated a better resolution not only with respect to the separation between healthy and CRC samples, but it is also able to discriminate samples with adenoma, being a promising tool for CRC prevention by detecting early stages in which intervention is easier and more effective. And finally, the model has a biological interpretation that provides important clues to better understand the mechanistic implications of the gut microbiota in CRC as well as in the previous stages of adenoma, which can have an interesting potential in preventive medicine and, specifically, in cancer interception [63].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it demonstrated a better resolution not only with respect to the separation between healthy and CRC samples, but it is also able to discriminate samples with adenoma, being a promising tool for CRC prevention by detecting early stages in which intervention is easier and more effective. And finally, the model has a biological interpretation that provides important clues to better understand the mechanistic implications of the gut microbiota in CRC as well as in the previous stages of adenoma, which can have an interesting potential in preventive medicine and, specifically, in cancer interception [63].…”
Section: Discussionmentioning
confidence: 99%
“…The complexity, diversity and pathways of precancer development and transformation causes great intra-and intertumor heterogeneity and individual variation. Emerging molecular and cellular studies exploiting advanced bigdata approaches are beginning map this complexity (33). Recent studies of colorectal and myeloproliferative neoplasia highlighted below have identified premalignant genomic subgroups, critical to refining preventive screening, risk stratification, and target identification (34).…”
Section: State Of Cancer Prevention Sciencementioning
confidence: 99%
“…It is, therefore, evident that, in clinical cancer management, tumor classifications cannot be uniformly applied across the world today. However, in the era of precision medicine and cancer genomics [5], the application of these internationally accepted classifications is considered obligatory as the starting point for cancer management. Clinical guidelines rating strength of evidence indicate which gene tests are recommended in defined clinical settings, and how management decisions are impacted by gene test results.…”
Section: Introductionmentioning
confidence: 99%